Water Relations and Physiological Traits Associated with the Yield Components of Winter Wheat (Triticum aestivum L.) - Katarzyna Juzoń-Sikora; Kamila Laskoś; Marzena Warchoł; Ilona Mieczysława Czyczyło-Mysza; Kinga Dziurka; Maciej Grzesiak; Edyta Skrzypek (Agriculture)
Water stress in agricultural systems may occur slowly or abruptly. Plant reactions to stress differ with regard to its level and duration. The level of plant susceptibility to water deprivation primarily depends on the management of the water content and metabolism adjustments. The aim of this study was to determine the correlation between water-based plant parameters and the yield components of 90 genotypes of winter wheat (Triticum aestivum L.). Since the loss of water is frequently used as a selection criterion to assess drought tolerance, the relationships between the yield and leaf water content, osmotic potential, and gas exchange characteristics were examined. Genotypes 1, 25, 34, 36, 42, 43, 46, 57, 66, 73, and 90 showed 33–45% larger numbers of grains/plant, 19–25% higher weights of grains/plant, and 4% higher thousand grain weights compared to other genotypes. The higher values of the yield components were accompanied by 20–30% lower leaf water content, 39–52% lower osmotic potential, and 4–39% lower water use efficiency. The principal component analysis revealed that the wheat genotypes had noticeable differences in a few physiological parameters that depended on the sowing date. Electrolyte leakage showed a substantial correlation with the sowing date, suggesting that it may not be a suitable factor for the prediction of drought tolerance. The factors that distinguished the examined genotypes the most were the leaf water content, osmotic potential, and water use efficiency. In addition, a significant correlation was observed between the mentioned parameters and yield components. As a result, these parameters may be helpful in genotype characterization in relation to water stress susceptibility, offering a trustworthy plant selection test.